ANALISA PELAKSANAAN AUDIT LINGKUNGAN ATAS PENGOLAHAN LIMBAH CAIR PADA PT. CHEVRON PACIFIC INDONESIA (Studi Kasus Limbah Air Terproduksi Lapangan Minas, Propinsi Riau) - - Hermiyetti; Arinta Satya Poetri (InFestasi, 2010)
Oil and gas companies have potential as a source of environmental pollution impacts, either directly or indirectly from any activities. Liquid, solid, and gas produced from primary production and its supporting activities are pollutants that can cause negative impacts on the environment.One of the biggest pollutants in oil and gas industry is water produced. Produced water is ground water as a byproduct in the production process of crude oil. Water produced with oil taken out toward the surface by bringing a variety of harmful compounds, so before disposal or use must first be processed and adapted to the existing quality standards.With the implementation of environment management systems, industry, through the identification of environmental impacts and environmental audit of internal activities that are conducted periodically, can create an environmental program with a priority scale of significance in terms of environmental impact. Of course, the industry can do environmental monitoring and evaluating the effectiveness of its implementation to achieve continuous improvement